Perancangan Sistem Informasi Sekolah Sebagai Media Promosi Berbasis Mobile - Rahayu, Sri Lestari (Publikasi Pengabdian Masyarakat, 2023)
Information technology is very developed in society, generally information technology is a technology that is used to manage data, process, store and manipulate data in various ways and procedures to produce quality and high-value information. Such technology is needed by SMK Tarbiyah Islamiyah Harapan Mekar Schools. It is school's hope to process new student data so that it can be stored in a database and make it easier for the school to carry out the process of registering new students. Manual or conventional registration systems that use physical forms are considered ineffective and efficient, many obstacles are faced including: requiring a lot of paper, prone to making mistakes or writing cannot be read, requires a lot of storage space, and takes a long time to find the desired data. This information system is also designed to assist the public in obtaining information about the SMK Tarbiyah Islamiyah Harapan Mekar School. This information system is designed on a mobile basis where using a mobile can make it easy for students, teachers and the public to find information anywhere and anytime. Because of this, the author carried out the activity of creating a school information system with students at the SMK Tarbiyah Islamiyah Harapan Mekar School. The Students have good will and competence in carrying out activities for making school information systems. This can be seen from the enthusiasm of the participants and the success in carrying out these activities. It is hoped that this activity can improve the ability of students to create school information systems, especially those used as promotional media